Sistem Control Sortir Makanan Menggunakan Android Sebagai Human Machine Interface (HMI) - Julianti Regita Merdi; Natanael Fernando; Pitoyo Yuliatmojo (LPPM Universitas Negeri Jakarta, 2016)
The final task was made with the aim of helping working an industrial unit in controlling and monitoring the sorting tools in the form of two types of food packaging food categories REJECT food and the food was OK. REJECT food category is when the packaging does not contain a full and when the food packaging containing metal and food categories OK is when the food is fully charged and does not contain metal. The design of control performed on prototype hardware horizontal conveyor models, for sorting it using two types of sensors. Led Photodioda and Proximity Sensors Cylindrical 8-8 DO which serves as the detection of metal or not in packs. For food packaging automatic separation systems using pneumatic system and the drive portion Conveyors selected DC motor, and controller used reley governed by Android technology as a human machine interface (HMI) and all will be controlled by an Arduino Mega 2560. With the Bluetooth module as a liaison between Android with Arduino Mega 2560 can be obtained that the tool will work in accordance with the job description of project tool that will be controlled using the Android. Tugas akhir dibuat dengan tujuan membantu kerja suatu unit industri dalam mengendalikan dan memonitor alat sortir makanan berupa 2 jenis kemasan makanan Kategori makanan REJECT dan makanan OK. kategori makanan REJECT adalah ketika kemasan tersebut tidak berisi penuh dan ketika kemasan makanan tersebut mengandung logam, dan kategori makanan OK adalah ketika makanan tersebut terisi penuh dan tidak mengandung logam. Rancanganan pengontrolan dilakukan pada hardware prototipe konveyor model horizontal, untuk penyortirannya menggunakan 2 jenis sensor. Sensor Photodioda Led dan Proximity Cylindrical 8 – 8 DO yang berfungsi sebagai deteksi adanya logam atau tidak dalam kemasan. Untuk sistem pemisahan otomatis kemasan makanan menggunakan sistem Pneumatik dan pada bagian penggerak konveyor dipilih Motor DC, dan pengendalinya digunakan relay yang diatur oleh teknologi android sebagai human machine interface (HMI) dan semua akan dikendalikan melalui sebuah arduino mega 2560. Dengan adanya modul Bluetooth sebagai penghubung antara android dengan arduino mega 2560 dapat diperoleh bahwa alat akan bekerja sesuai dengan deskripsi kerja dari project alat yang akan di kendalikan menggunakan Android.